2011
DOI: 10.3109/01460862.2011.572638
|View full text |Cite
|
Sign up to set email alerts
|

“I Want to Meet Other Kids Like Me”: Support Needs of Children with Asthma and Allergies

Abstract: Parents and children preferred a combination of in-person meetings and Internet support to enhance the capacity of children, reduce children's anxiety, increase their self-care skills, and self-confidence. In addition they believed a support intervention was a stepping stone to developing a community of support for children with asthma, allergies, and anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 34 publications
2
73
0
1
Order By: Relevance
“…Similarly, Stewart's 2011 study revealed that 19 out of 20 children expressed a desire for peer support when dealing with asthma or severe allergies [60]. A second study by Stewart that same year revealed that 73.7% of children 11 to 16 years (n=28) participating in an online chat group designed to bolster peer support of children suffering with asthma felt that the open and supportive atmosphere was beneficial to their feelings of emotional well-being and social inclusion [45]. Adolescents in this study reported benefiting from communication and mutual affirmation with similar individuals [45].…”
Section: Peer Influencementioning
confidence: 98%
See 4 more Smart Citations
“…Similarly, Stewart's 2011 study revealed that 19 out of 20 children expressed a desire for peer support when dealing with asthma or severe allergies [60]. A second study by Stewart that same year revealed that 73.7% of children 11 to 16 years (n=28) participating in an online chat group designed to bolster peer support of children suffering with asthma felt that the open and supportive atmosphere was beneficial to their feelings of emotional well-being and social inclusion [45]. Adolescents in this study reported benefiting from communication and mutual affirmation with similar individuals [45].…”
Section: Peer Influencementioning
confidence: 98%
“…Additionally, research suggests that parental care of infants and toddlers results in higher levels of socio-emotional and cognitive development than that of children in institutionalized care [48]. The primary position of parents as teachers and supporters is evidenced in a qualitative study of children ages six through 12 (n=20), where children with asthma reported that their mothers were their primary source of support [45]. Even in adolescence, high parental support and low levels of negative parental controls are indicators of higher levels of social acceptance and in-group status when compared to low parental support or presence [49].…”
Section: Parental Supportmentioning
confidence: 99%
See 3 more Smart Citations